2006
DOI: 10.1634/theoncologist.11-2-165
|View full text |Cite
|
Sign up to set email alerts
|

Changing Paradigms—An Update on the Multidisciplinary Management of Malignant Glioma

Abstract: Learning ObjectivesAfter completing this course, the reader will be able to:1. List the different major subtypes of glioma and identify the appropriate treatment strategies for patients with high-grade and low-grade gliomas.2. Discuss the available evidence for the treatment of newly diagnosed glioblastoma, anaplastic astrocytoma, and anaplastic oligodendroglioma.3. Identify approved agents and other active or investigational agents used to treat patients with newly diagnosed and recurrent glioma. shown that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
241
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(265 citation statements)
references
References 116 publications
(126 reference statements)
5
241
0
9
Order By: Relevance
“…Although it has been shown earlier that PI-103 has an anti-proliferative effect on GBM cells as a single agent (Fan et al, 2007) or in combination with the epidermal growth factor receptor inhibitor erlotinib (Fan et al, 2006), and that it enhances tumor radiosensitivity (Prevo et al, 2008), no study has so far addressed the potential interaction between chemotherapeutic agents and PI-103. This is of particular interest for GBM, for which the current standard of care is still considered to be a surgical resection of the tumor mass, a frequently unsuccessful and difficult procedure (Stupp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been shown earlier that PI-103 has an anti-proliferative effect on GBM cells as a single agent (Fan et al, 2007) or in combination with the epidermal growth factor receptor inhibitor erlotinib (Fan et al, 2006), and that it enhances tumor radiosensitivity (Prevo et al, 2008), no study has so far addressed the potential interaction between chemotherapeutic agents and PI-103. This is of particular interest for GBM, for which the current standard of care is still considered to be a surgical resection of the tumor mass, a frequently unsuccessful and difficult procedure (Stupp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although the care of GBM patients is usually multidisciplinary and includes surgery, radiotherapy and chemotherapy (Stupp et al, 2006), current treatment regimens have so far failed to significantly increase median survival after diagnosis, which is o12 months (Ohgaki et al, 2004). This highlights the need for novel and improved therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Current therapy includes surgery, radiation and chemotherapy. However, these tumours show resistance to chemotherapy and radiation (Stupp et al, 2006). We were interested in elucidating strategies to enhance cell death in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of patients is not cured by surgical resection, and tumors usually recur in a distance of less than 2 cm from the initial site (37). However, the goal to attempt gross total tumor removal is generally accepted.…”
Section: Current Therapeutic Options For Glioblastomamentioning
confidence: 99%
“…One of the newer drugs that have been used in recurrent glioma is irinotecan (Camptosar, Pfizer Pharmaceuticals), a topoisomerase I inhibitor with good penetration of the blood-brain barrier. Several clinical trials were conducted and showed response rates from 2.2% to 16% (37,50,51). Progression-free survival after 6 months was reported to be 25% to 43% in some studies (50,51).…”
Section: Current Therapeutic Options For Glioblastomamentioning
confidence: 99%